1960
DOI: 10.1136/gut.1.3.258
|View full text |Cite
|
Sign up to set email alerts
|

Surgery in Bleeding Peptic Ulcers

Abstract: This paper records a study of 400 patients admitted for haematemesis and melaena. Emergency surgery was undertaken on selected patients but the overall mortality increased when more frequent emergency operations were performed in the latter half of the series.The proper management of haematemesis and melaena is a constantly recurring problem. Our material consists of 473 patients admitted for haematemesis and melaena between January, 1953, and July, 1958. Four hundred of these (87%) were for proved or suspect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
6
0
2

Year Published

1967
1967
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 38 publications
2
6
0
2
Order By: Relevance
“…This serious situation faced 20% of all the patients in the series and 25-8% of 511 patients in the peptic ulcer group. These proportions are very similar to those reported by Jones (1956) in 1,414 admissions and Ward-McQuaid et al (1960) in 400 admissions for bleeding peptic ulcer. This group is therefore both numerous and dangerous.…”
Section: Discussionsupporting
confidence: 88%
“…This serious situation faced 20% of all the patients in the series and 25-8% of 511 patients in the peptic ulcer group. These proportions are very similar to those reported by Jones (1956) in 1,414 admissions and Ward-McQuaid et al (1960) in 400 admissions for bleeding peptic ulcer. This group is therefore both numerous and dangerous.…”
Section: Discussionsupporting
confidence: 88%
“…The overall mortality in the present series is 12%, which compares with 14.3% reported by Ward-McQuaid et al (1960) in a similar group treated by partial gastrectomy. Our mortality when using conservative surgery was 7% compared with 18% for radical surgery.…”
Section: Methods and Resultssupporting
confidence: 44%
“…Variations in the reported mortality can be accounted for by differences in the cases studied. The average mortality in patients with moderate ro severe haemorrhage from all types of ulcer treated by partial gastrectomy is probably nearer 15 % (Ward-McQuaid, Pease, Smith, and Twort, 1960). Smith and Farris (1958) suggested that this might be reduced by a more conservative operation in duodenal ulcer consisting in direct suture of the bleeding vessel with vagotomy and a gastric drainage procedure.…”
mentioning
confidence: 99%
“…Following medical management over 70% of peptic ulcer bleeds and 44% of variceal bleeds resolved with no further bleeding. 52,53 Surgery was mostly reserved for those with unstable ulcer bleeding, whereas other causes such as varices and gastric cancer where not amenable to emergency treatment.…”
Section: Mortality Trends 231 Natural Historymentioning
confidence: 99%